RADICAL FEMINISM IN “BARBIE THE MOVIE (2023)” BY GRETA GERWIG - Tsabitah Az-Zahra Syawaluddin; Sahril Nur; Yunitari Mustikawati (State University of Makassar, 2026)
This study examines the representation of radical feminism in Barbie the Movie (2023) directed by Greta Gerwig using Mackay's (2015) theory of radical feminism. The research focuses on how the film represents the major principles of radical feminism and challenges common misconceptions surrounding the movement. Using a qualitative textual analysis, this study analyzes dialogues, character interactions, visual representations, and narrative elements in the film. The findings reveal that Barbie the Movie represents the four major principles of radical feminism: the existence of patriarchy, women-only spaces, male violence against women, and the rejection of women's objectification. The film also challenges common misconceptions by demonstrating that radical feminism critiques patriarchal systems rather than men, presents women-only spaces as forms of political solidarity rather than anti-male exclusion, rejects the belief that all men are inherently violent, and shows that radical feminism does not oppose femininity itself. This study contributes to feminist film studies by providing a deeper understanding of how contemporary popular cinema represents radical feminist ideas and addresses public misconceptions about the movement. Keywords: Barbie the Movie (2023), radical feminism, Mackay, Misconceptions.